Advanced paediatric life support : the practical approach - Samuels, Martin (Martin P.); Wieteska, Susan; Advanced Life Support Group (Manchester, England); Wiley InterScience (Online service) (Chichester, West Sussex, UK : BMJ Books, 2011)
This internationally acclaimed bestseller covers the ALSG's three-day course on advanced paediatric life support, with the core sections for the abbreviated one-day course also highlighted. It provides practical guidance for managing children and infants in the life-threatening first golden hour, presenting the first principles of recognising life threatening conditions through all the procedures necessary to save a child's life. This new edition includes the 2010 European Resuscitation Council Guidelines, and the Royal College of Paediatrics and Child Health new neurological guidelines. It also includes sections on stabilisation and transfer, BestBETs and other evidence-based references throughout, as well as updated material at www.alsg.org.uk --Provided by publisher.
Machine generated contents note: Clinical Conditions List. -- Working Group. -- Contributors. -- Preface to the Fifth Edition. -- Preface to the First Edition. -- Acknowledgements. -- Contact Details and Further Information. -- PART I: INTRODUCTION. -- Chapter 1 Introduction. -- Chapter 2 Why treat children differently?. -- Chapter 3 Structured approach to emergency paediatrics. -- PART II: LIFE SUPPORT. -- Chapter 4 Basic life support. -- Chapter 5 Advanced support of the airway and ventilation. -- Chapter 6 The management of cardiac arrest. -- PART III: THE SERIOUSLY ILL CHILD. -- Chapter 7 The structured approach to the seriously ill child. -- Chapter 8 The child with breathing difficulties. -- Chapter 9 The child in shock. -- Chapter 10 The child with an abnormal pulse rate or rhythm. -- Chapter 11 The child with a decreased conscious level. -- Chapter 12 The convulsing child. -- PART IV: THE SERIOUSLY INJURED CHILD. -- Chapter 13 The structured approach to the seriously injured child. -- Chapter 14 The child with chest injury. -- Chapter 15 The child with abdominal injury. -- Chapter 16 The child with trauma to the head. -- Chapter 17 The child with injuries to the extremities or the spine. -- Chapter 18 The burned or scalded child. -- Chapter 19 The child with an electrical injury or drowning -- PART V: PRACTICAL APPLICATION OF APLS. -- Chapter 20 Practical procedures -- airway and breathing. -- Chapter 21 Practical procedures -- circulation. -- Chapter 22 Practical procedures -- trauma. -- Chapter 23 Interpreting trauma X-rays. -- Chapter 24 Structured approach to stabilisation and transfer. -- Chapter 25 Human factors. -- PART VI: APPENDICES. -- Appendix A Acid. -- Appendix B Fluid and electrolyte management. -- Appendix C Child abuse. -- Appendix D Prevention of injury in children. -- Appendix E When a child dies. -- Appendix F Management of pain in children. -- Appendix G Triage. -- Appendix H General approach to poisoning and envenomation. -- Appendix I Resuscitation of the baby at birth. -- Appendix J Formulary. -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Pediatric emergencies; Pediatric intensive care; Life support systems (Critical care); Emergencies; Child; Critical Care -- methods; Emergency Treatment -- methods; Infant; Wounds and Injuries -- therapy; Life support systems (Critical care); Pediatric emergencies; Pediatric intensive care; Electronic books